Political Perspective in Geo-Map Analysis: What is the Role of World Governance Indicators in Reducing Greenhouse Emission in ASEAN Countries? - Ratnadewati, Ainina; Gravitiani, Evi; Widiastuti, Nur; Wicaksono, Arsetho Teguh (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to analyze whether world governance indicators can reduce greenhouse gas emissions in ASEAN countries. The data used is panel data of 11 ASEAN member countries in the period 2013 – 2020 with justifications before and after the Paris Agreement with panel regression methods and mapping using orange data mining geo maps. Empirical results show that political stability no violence, government effectiveness, corruption control, and the implementation of the Paris Agreement are able to reduce the amount of greenhouse gas emissions. It was concluded that the success of the Paris Agreement will occur when committed countries dare to carry out economic transformation. However, to achieve this, significant adjustments are needed, and all parties must have a uniform vision for achieving the net zero carbon target.